Belarus : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in the Republic of Belarus during the 1990s. In late 1994 and early 1995, the Belarusian authorities took major steps to further liberalize the economy and bring down inflation from the high levels of 1993-94. By the second half of 1995, however, macroeconomic policies began to be relaxed and structural reform came to a virtual standstill. The relaxation of monetary policy was accompanied by an exchange rate policy in 1996, which caused the Belarusian currency to continue to appreciate significantly against the U.S. dollar.